Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s12672-021-00448-z
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-26a represses pancreatic cancer cell malignant behaviors by targeting E2F7

Abstract: Dysregulation of microRNAs (miRNAs) exerts key roles in the development of pancreatic cancer (PCa). miR-26a is reportedly a tumor suppressor in cancers. However, whether miR-26a modulates PCa progression is poorly understood. Here, we found that miR-26a was down-regulated in PCa. Overexpressed miR-26a suppressed PCa cell proliferation, colony formation, and tumor stem cell properties. Mechanically, the transcription factor E2F7 is a downstream target of miR-26a. miR-26a decreased E2F7 expression through bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Pancreatic ductal carcinoma shows > 70% inactivation of the tumour suppressor p53 [47,48]. To verify the potential clinical relevance of p53-nuclear pore and p53-nuclear lamina axes in PDAC, we examined the expression of the members of these two families in a dataset of nearly 200 PDAC-patients.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic ductal carcinoma shows > 70% inactivation of the tumour suppressor p53 [47,48]. To verify the potential clinical relevance of p53-nuclear pore and p53-nuclear lamina axes in PDAC, we examined the expression of the members of these two families in a dataset of nearly 200 PDAC-patients.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are needed to establish the role of miR-7704 in cancer, especially in cervical cancer. The tumor suppressor activity of miR-26a-5p in cancer has been extensively described in many studies and has great potential in diagnostics ( 46 48 ). Rather, some studies have already addressed its therapeutic potential and identified its target mRNA in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 could be served as an excellent target for cancer immunotherapy, and DKK1-CKAP4-PI3K/AKT signal pathway also plays a pivotal role in the proliferation of PC 46 . By targeting E2F7, miR-26a inhibited the malignant behaviors of PC cells 47 . In pancreatic adenosquamous carcinoma, EGFR-associated ligand-receptor pairs are activated in cell communications at a single-cell transcriptomics level 48 .…”
Section: Discussionmentioning
confidence: 99%